2022
DOI: 10.1088/1674-1056/ac29b3
|View full text |Cite
|
Sign up to set email alerts
|

A broadband self-powered UV photodetector of a β-Ga2O3/γ-CuI p-n junction

Abstract: The symmetric Ti/Au bi-layer point electrodes have been successfully patterned on the β-Ga2O3 films which are prepared by metal–organic chemical vapor deposition (MOCVD) and the γ-CuI films which are prepared by spin-coating. The fabricated heterojunction has a large open circuit voltage (V oc) of 0.69 V, desired for achieving self-powered operation of a photodetector. Irradiated by 254-nm ultraviolet (UV) light, when the bias voltage is –5 V, the dark current (I dark) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Many materials have been reported to form heterojunctions with Ga 2 O 3 , such as graphene, Ti 3 C 2 , BiFeO 3 , CsCu 2 I 3 , PEDOT:PSS, WO 3 , CuI, and ZnO. [15][16][17][18][19][20][21][22][23] Li's research confirmed that a heterostructure PD possesses a certain improvement in light response compared with a single-material PD. [24] The rise and decay times of Ga 2 O 3 /CuSCN heterojunction photodetectors are 0.19 s and 0.16 s, faster than those of independent CuSCN and Ga 2 O 3 devices, indicating that the constructed n-Ga 2 O 3 /p-CuSCN heterojunction can effectively improve the photoresponse speed.…”
Section: Introductionmentioning
confidence: 95%
“…Many materials have been reported to form heterojunctions with Ga 2 O 3 , such as graphene, Ti 3 C 2 , BiFeO 3 , CsCu 2 I 3 , PEDOT:PSS, WO 3 , CuI, and ZnO. [15][16][17][18][19][20][21][22][23] Li's research confirmed that a heterostructure PD possesses a certain improvement in light response compared with a single-material PD. [24] The rise and decay times of Ga 2 O 3 /CuSCN heterojunction photodetectors are 0.19 s and 0.16 s, faster than those of independent CuSCN and Ga 2 O 3 devices, indicating that the constructed n-Ga 2 O 3 /p-CuSCN heterojunction can effectively improve the photoresponse speed.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Tang et al studied p-NiO/n-Ga 2 O 3 photodetectors; under zero bias, the device responsivity was 57 μA/W, and its detectivity was 5 × 10 9 Jones . Based on the Schottky, heterojunction, or p–n junction designs, photodetectors can use the associated built-in electric field to separate and transport photogenerated carriers, which possess obvious advantages of no need of external driving electric source, fast response, and easy integration. …”
Section: Introductionmentioning
confidence: 99%
“…8–11 Yet, CuI is far from being fully exploited as a transparent p-type semiconductor and further study is still required toward improved properties and possible applications. So far, CuI has been reported to be integrated with ZnO, 12–16 Ga 2 O 3 , 17,18 TiO 2 , 19,20 IGZO, 21 n type Si (n-Si), 22 etc. to construct CuI-based ultraviolet (UV) photodetectors.…”
Section: Introductionmentioning
confidence: 99%